ESENSI DAN URGENSI NILAI-NILAI MAQASHID SYARIAH DALAM KURIKULUM MERDEKA - Qomaria, Elysa Nurul; Mustofa, Ali (Sasangga: Jurnal Pendidikan dan Pembelajaran, 2024)
This study examines the integration of Maqashid Syariah values into Indonesia's Merdeka Curriculum as a framework for harmonizing national education with Islamic principles. By employing the five core dimensions of Maqashid Syariah, protection of religion, intellect, life, wealth, and progeny as evaluative lenses, this research analyzes the extent to which the current curriculum aligns with these foundational goals. Utilizing a descriptive-qualitative method with content analysis, findings indicate that although the Merdeka Curriculum emphasizes holistic student development and independent learning, its alignment with Maqashid Syariah values remains largely untapped. The study affirms that adopting the Maqashid paradigm can enrich curriculum discourse and provide a contextualized direction for Islamic education in Indonesia.